Estimation of the population size of Capoeta umbla (Heckel, 1843) In the Lake Hazar (Elazig) by removal method - Yüksel, F.; Alp, A.; Gündüz, F.; Zülfü Çoban, M.; Demirol, F. (Inst Materials Physics, 2014)
Fish populations in smaller aquatic environments are affected by the fishing pressure at a much faster pace. Often, compensation of this effect either takes a long time or is not possible at all. For the purposes of establishing fishing regulations in these water environments, the removal method is able to provide results quickly and almost accurately. The Lake Hazar, which is the environment of our study, is 8,600 hectares in size, and is a natural lake where Capoeta umbla species is caught commercially using gill nets. In this study, stock size of Capoeta umbla in the Lake Hazar (Elazig) was estimated using removal method. In addition, the power of fishing and the status of fishing yield in the lake were evaluated. In our research, it was determined that seven commercial fishing boats caught 25,721 kg of fish in the lake in a fishing season. CPUE was calculated as 1.55 kg (kg/day/a gill net). As a result of the regression analysis, the amount of stock in the lake was the estimated to be 37,781 kg (± 14,001 kg). When cumulative catch was formulated as recommended by Ricker (1975), the population size was estimated to be 38,649 kg (± 15,007 kg). As a result of our study, the use of removal method was found to be appropriate for small reservoirs with reduced population density due to strong fishing pressure.
Keywords: Capoeta umbla; CPUE; Lake Hazar; Removal Method; Stock Assessment